Long-Term Treatment Outcomes of the Elder Patients with Locally Advanced Thoracic Esophageal Squamous Cell Carcinoma with Definitive Chemoradiotherapy or Radiotherapy. (16th July 2022) - Liu, Junqing; Li, Yishuang; Chen, Ying; Jiang, Xue; Yu, Haogang; Yan, Senxiang
Abstract : Background . Few randomized trials are available to guide clinical management of elderly patients with esophageal cancer. Therefore, treatment approaches for the elderly are challenging. Objective . We believe that chemotherapy and radiotherapy are more effective than radiotherapy alone. We envision that chemotherapy is more effective than radiotherapy alone in elderly patients with esophageal cancer. Methods . Retrospective data of patients aged 70 years and older from 2008 to 2015 at our institution were analyzed. Of 61 eligible patients, 32 received definitive CTR and 29 received RT alone. Progression-free survival (PFS) was 16 months (range, 1–67 months), and the median overall survival was 19 months. Median PFS and OS in the chemoradiotherapy group were 17 months (95% confidence interval (CI), 15.1–24.8 months) and 22 months (95% confidence interval (CI), 20.4–32.7 months), respectively. Results . The median PFS and OS in the radiotherapy group were 16 months and 16 months, respectively. The OS rates at 1, 2, 3, and 5 years were 82%, 42.6%, 19.7%, and 6.6%, respectively. There was no difference in PFS between CRT and RT, but there was an advantage in OS for CRT. Positive nodules had an effect on PFS and OS. Conclusions . CRT is effective in elderly patients with nodal invasion of esophageal cancer. Higher radiation doses had an effect on PFS and OS, but there was no difference in PFS and OS between CRT and RT. Therefore, treatment approaches for the elderly are challenging.